(untitled) (TAMADDUN NURI JURNALI, 2024)
The article analyzes views on the textual roots of the series of epics “Bird’s Language”, polished over centuries. Their fundamental essence and the Islamic-mystical spirit embodied in them are described, aspects of the promoted good ideas related to the era.